THE CONTRIBUTION OF CREATIVE WRITING ACTIVITY TOWARD STUDENT’S ENGAGEMENT IN POETRY CLASS - Gina Larasaty; Ida Yulianawati (Wiralodra English Journal, 2019)
Consider the Creative writing is very popular rightnow, the researcher tried to investigated the Students’ engagement through Creative writing activities. This study investigated how far the creative writing will engage the students’ in learning poetry. The participant of this study was students in fourth semester of English Department in Wiralodra University. Therefore, this qulitative study sets out to investigate the students’ engagement in doing Creative writing activities in poetry Class.The findings suggest that Creative writing activities is able to engage students in poetry classroom. Then emotional engagement ( M= 32,63) is dominated followed by behavioral engagement ( M= 17.24) and cognitive engagement (M = 15,24 ). So it means Emotional engagement from their perspective has more to do with the pleasant and unpleasant emotions students connect to the activity and behavioral engagement focused on their effort but as cognotively not. In other words, they have effort to simply do the work but cannot focused on understanding and mastery. However this result showed that emotional engagement dominated in students engagement in poetry class, cognitive and behavioural still showed the positive engagement in poetry class.